The Role of Dry Needling in Complex Regional Pain Syndrome Management: A Mini Review - I Putu Eka Widyadharma; Aurelia Vania; Bryan Gervais de Liyis; Ni Luh Putu Saswatasya Widha Putri; Jimmy Fransisco Abadinta Barus; Boya Nugraha (Traditional and Integrative Medicine)
Complex Regional Pain Syndrome (CRPS) presents as a multifaceted condition characterized by pain, autonomic dysregulation, and motor dysfunction. Within the realm of pain management, Dry Needling (DN) emerges as a promising therapeutic modality. This systematic review assesses the role of DN in the management of CRPS, with a focus on pivotal outcomes encompassing pain intensity, disability, and musculoskeletal factors. Our systematic review encompassed rigorous searches through PubMed, Scopus, Web of Science (WoS), Cochrane Library, ScienceDirect, and Google Scholar, spanning studies up to January 2023, without language constraints. Four studies meeting predetermined inclusion criteria were identified, collectively encompassing a cohort of 47 patients afflicted with unilateral upper limb CRPS Type I. Following DN, a palpable reduction in pain intensity was ubiquitously observed among all subjects. Furthermore, assessments employing the Disabilities of the Arm, Hand, and Shoulder (DASH) score indicated a substantial reduction in disability levels post-DN intervention. Impressively, musculoskeletal ultrasonography underscored an amelioration in muscle condition, concomitant with discernible enhancements in motor function disturbances post-DN. These compelling findings suggest that DN may substantively complement a multimodal CRPS management paradigm. DN has the capacity to target the fundamental issue of motor function impairment while concurrently promoting pain relief and reducing disability in the intricate context of CRPS.